Nusantara Capital City Development: From Agrarian Conflict Potential to Legal Protection of Indigenous Peoples - Putra, Naufal Dekananda Anggara; Anggraeni, Happy Yulia; Ridwan, Ahmad M.; Jamaludin, Ahmad (Reformasi Hukum, 2025)
Developing Indonesia’s new capital city, Nusantara (IKN) in East Kalimantan, has the potential to significantly impact indigenous communities, particularly in agrarian conflicts arising from expanding development land that intersects with indigenous territories. This study aims to analyze the potential agrarian conflicts and adequate legal protections for indigenous peoples in addressing these impacts. The method is normative juridical, with data collected through library research on relevant regulations, literature, and studies. The findings show that agrarian conflicts resulting from the IKN development may arise due to the mismatch between the legal recognition of Indigenous land rights and the allocation of development land that does not actively involve Indigenous communities. Legal protection for indigenous peoples can be achieved by recognizing land rights, strengthening agrarian regulations that are more responsive to indigenous rights, and implementing the Free, Prior, and Informed Consent (FPIC) principle in the planning and management of IKN development. The conclusion of this study emphasizes the importance of recognizing indigenous land rights and involving them in every stage of development to prevent agrarian conflicts and create more equitable development policies.